Nationalist mobilization and the collapse of the Soviet State - Beissinger, Mark R. (Cambridge studies in comparative politics., 2002)
This study examines the process of the disintegration of the Soviet state. The author uses data and case studies from across the USSR to elicit the shifting relationship between existing structural conditions and institutional constraints.